Penerapan Mutu Layanan Dalam Merambah Peluang Prestasi Sekolah Berbasis Pesantren - Sofwatillah, Sofwatillah; Mukhtar, Mukhtar; Anwar, Kasful; MY, Mahmud; Asrulla, Asrulla (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
Islamic boarding school (SBP) is a model of Islamic education that integrates two systems, namely the superiority of the social system and Islamic boarding school curriculum and the superiority of the general system. This Islamic education model can create people who are religious as well as scientists, so that they can play a full role in the system that exists in society. This research aims to describe how Service Quality is implemented in expanding Islamic boarding school-based school achievement opportunities. The results that will be examined are as follows: (1) Quality of Service in expanding the Achievement Opportunities for Islamic Boarding School-Based Schools. (2) Planning for the quality of educational services is in the good category by involving related parties: school principals, Islamic Boarding School Directors, teachers' councils, Musyrif (Student Supervisor), administrative staff, school committees and school supervisors, (3) Implementation of service quality in expanding opportunities for achievement. (4) Improving the quality of educational services is carried out continuously through identifying improvement processes and methods, forming a team tasked with carrying out improvements and providing resources and training. This research uses a qualitative method with a case study approach.